THE LANGUAGE LEARNING TASK: TASK-BASED LEARNING, CONTENT-BASED LEARNING, AND PROJECT-BASED LEARNING (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper investigates three foundational methodologies that have gained prominence in the field of contemporary language education: Task-Based Learning (TBL), Content-Based Learning (CBL), and Project-Based Learning (PBL). These learner-centered approaches foreground authentic communication, foster learner autonomy, and promote experiential learning as central to language acquisition. Drawing on relevant theoretical frameworks, this study critically examines the pedagogical rationales, educational advantages, and potential limitations associated with each model. Furthermore, it offers a comparative analysis that highlights their complementary features. In doing so, the article advocates for a cohesive and integrative instructional model that leverages the strengths of each approach to enhance linguistic competence and pedagogical effectiveness in diverse educational settings.